Cowpea Yield Under Water Stress Scenarios - Ferreira, Francisco Edson Paulo; Silva, Vicente de Paulo Rodrigues da; Silva, Madson Tavares; Dantas, Sílvia Maria (Anuário do Instituto de Geociências, 2023)
Cowpea is considered a subsistence crop, so it is generally cultivated by family farming in the rainy season and, outside this season, with the aid of irrigation. Its yield is reduced if there is water stress due to the lack of rainfall or irrigation water. Objective of this study was to evaluate the influence of water stress in the rainy and dry seasons on grain yield, biomass, harvest index and water use efficiency in the ‘Costela de Vaca’ cowpea variety cultivated in no-tillage system using crop residues present in the experimental area. Experimental design used was randomized blocks, in a 2 x 5 factorial scheme (cropping season x water stress), with four replicates. Treatments consisted of two cropping seasons (rainy and dry) and five forms of water stress (without water stress, water suspension for 5, 10 and 15 days, and rainfed cultivation). Biomass was the only parameter influenced by the cropping season versus water stress interaction. Regardless of the cowpea cropping season, water stress reduced grain yield and biomass. Harvest index showed no sensitivity to water stress and cropping season. Water use efficiency was influenced by the cropping season. Soil cover promoted maintenance of soil moisture during cowpea cultivation in both periods.